Brain stimulation enhances dispositional mindfulness in PTSD: an exploratory sham-controlled rTMS trial - Rayani, Kaveh; Grabovac, Andrea; Chan, Peter; Montgomery, Stefanie; Ghovanloo, Mohammad-Reza; Sacchet, Matthew D. (Frontiers in Psychiatry, 2025)
ObjectivePost-traumatic stress disorder (PTSD) is characterized by hypervigilance, intrusive thoughts, negative mood, and avoidant behaviors. Therapies involving mindfulness have been shown to reduce PTSD symptoms and modulate brain function. Pharmacological and brain stimulation interventions are also effective for treating PTSD. Non-invasive repeated transcranial magnetic stimulation (rTMS) of the dorsolateral prefrontal cortex (DLPFC) has been shown to regulate mood and improve PTSD symptoms.MethodsThis is a retrospective chart analysis of data collected pre-treatment, post-treatment, and at three-month follow-up in a single-site, double-blind, sham-controlled trial of right DLPFC rTMS. 31 participants diagnosed with PTSD were recruited for this pilot study. Over two weeks, 19 participants received ten sessions of either 1 Hz or 10 Hz stimulation, and nine received sham treatment.ResultsParticipants in the rTMS group had a significant reduction in total Five Facet Mindfulness Questionnaire (FFMQ) scores from baseline to post-treatment, this difference was no longer observed when a false discovery rate (FDR) correction was applied. However, a significant improvement was observed in the rTMS group from baseline to the three-month follow-up in total FFMQ score and nonreactivity. This change in mindfulness scores suggests a potential delay in onset of benefits.ConclusionsBased on our preliminary data, rTMS may improve levels of dispositional mindfulness and its specific subcomponents. Future studies could investigate brain stimulation to assess its utility for improving mindfulness and related health outcomes to reduce suffering related to PTSD. Moreover, application of this neurostimulation modality for improving mental illness and well-being more generally merits further exploration.Clinical trial registrationhttps://clinicaltrials.gov/study, identifier NCT01806168.